2014
DOI: 10.1021/jo402742k
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Domino Addition/Double Cyclization: An Approach to Polycyclic Benzimidazole Derivatives

Abstract: An efficient and versatile method for the assembly of novel polycyclic benzimidazole derivatives has been developed by Cu-catalyzed domino addition/double cyclization reactions. A wide variety of polycyclic benzimidazole derivatives, which might be used as synthetic medicines and functional materials, were successfully assembled from bis-(o-haloaryl)carbodiimides. Unexpected N-methylated benzo[4,5]imidazo[1,2-a]indoles can also be selectively assembled. Multibonds and polycyclic moieties were conveniently form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Furthermore, a one-pot approach to indolo[1,2-f]-phenanthridines from o-alkynylanilines and 1,2-dihaloarenes has not been achieved until now. As part of our ongoing research efforts toward the domino synthesis of heterocycles under copper catalysis, 27,[37][38][39][40] we became interested in applying the one-pot protocol to the assembly of 1,2-disubstituted indoles and the tandem synthesis of indolo[1,2-f]phenanthridines. The findings are reported herein.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a one-pot approach to indolo[1,2-f]-phenanthridines from o-alkynylanilines and 1,2-dihaloarenes has not been achieved until now. As part of our ongoing research efforts toward the domino synthesis of heterocycles under copper catalysis, 27,[37][38][39][40] we became interested in applying the one-pot protocol to the assembly of 1,2-disubstituted indoles and the tandem synthesis of indolo[1,2-f]phenanthridines. The findings are reported herein.…”
Section: Methodsmentioning
confidence: 99%
“…[1] During the course of our continuous efforts directed toward developing new synthetic methods for polynuclear N-fused hybrid scaffolds under transition metal-catalyzed and transition metal-free conditions, [2] we reported on the synthesis of trinuclear N-fused hybrid scaffold A by basepromoted double C(sp 2 )-N coupling between 2-(2-bromoaryl)benzimidazoles and 2-aminobenzimidazole under transition metal-free condition (Scheme 1, route a). [3,4] The present work started during the course of application of such a protocol to the reaction with indole analogues to form trinuclear N-fused hybrid scaffolds, benzo [4,5]imidazo [1,2-c]indolo [1,2-a]quinazolines B (Scheme 1, route d). In contrast to widely known synthetic methods and biological activities of each homonuclear scaffold (indole, quinazoline, and benzimidazole) of scaffold B and binuclear scaffolds by the combination of such a homonuclear scaffold, only one report is found for the synthetic method of their trinuclear N-fused hybrid scaffold B.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to widely known synthetic methods and biological activities of each homonuclear scaffold (indole, quinazoline, and benzimidazole) of scaffold B and binuclear scaffolds by the combination of such a homonuclear scaffold, only one report is found for the synthetic method of their trinuclear N-fused hybrid scaffold B. [5] Lv and co-workers reported that bis(o-iodophenyl)carbodiimide reacted with indoles in the presence of CuI and 1,10-phenanthroline to produce scaffold B via sequential processes such as nucleophilic addition, tautomerization, Ullmann-type C-N coupling, and intramolecular C(sp 2 )-H arylation (Scheme 1, route b). [5] Herein this report shows another example for the synthesis of trinuclear N-fused hybrid scaffold B by CuI-catalyzed double C(sp 2 )-N coupling between 2-(2-bromoaryl)indoles and 2-aminobenzimidazole with broad substrate scope under microwave irradiation (Scheme 1, route d).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common strategy for accessing benzimidazoquinazolines is the construction of CÀ N bonds by Ullmann-type reactions or Buchwald couplings. [10] Lv's group [11] reported the synthesis of fused quinazolines through a Cu-catalyzed addition/double cyclization cascade from bis-(o-haloaryl)carbodii-mides (Scheme 1, eq 1). Kumar's group and Chen's group [12] separately reported a procedure for the synthesis of novel azole-fused quinazolines via a Pd/Cu co-catalyzed or Cu catalyzed, Ullmann-type coupling followed by cross-dehydrogenative coupling of various azoles with 2-(2-bromophenyl)-1Himidazole/benzimidazoles (Scheme 1, eq 2).…”
Section: Introductionmentioning
confidence: 99%